(untitled) (International Journal of Mathematics and Physics, 2016)
Interaction potentials of electrons and ions with dust particles are developed to consistently treat plasma electrodynamics. It is assumed for the sake for simplicity that the material, the dust particles are made of, is a perfect conductor, and, then, the linear density-response formalism in the random phase approximation is used to take into account finite dimensions of grains. Additionally, the number density of protons is kept fixed such that the negative electric charge is allocated between the free electrons and the dust particles to assure the whole quasineutrality of the system. On the ground of the developed interaction potentials the electric charge of the dust particles is then calculated within the orbital motion limited (OML) approximation, which stems from the ballistic trajectories of the plasma particles at the charging process. It is rather clear that to advocate such a technique the mean free paths of the plasma particles must be much greater than the dimension of the dust grain. It is well known that under OML assumptions the conservation laws of energy and angular momentum are sufficient to determine the absorption cross sections of electrons and ions by the dust particle. The resultant absorption cross sections are then integrated over the velocity distribution distribution function to evaluate the fluxes of plasma particles on the grain surface, and the electric charge of the dust particle is stabilized when those fluxes are finally equalized. G M T Английский Испанский Итальянский Казахский Китайский Трад Китайский Упр Корейский Русский Турецкий Французский Английский Испанский Итальянский Казахский Китайский Трад Китайский Упр Корейский Русский Турецкий Французский Звуковая функция ограничена 200 символами Настройки : История : Обратная связь : Donate Закрыть